2011
DOI: 10.1093/tropej/fmr009
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Dysfunction in HIV-infected Children in a Sub-Saharan African Country: Comparative Cross-sectional Observational Study

Abstract: Structural and functional abnormalities are prevalent in HIV-infected African children and therefore justify inclusion of routine echocardiography in their standard care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 21 publications
5
45
1
Order By: Relevance
“…Ventricular dimensions and mass are large in PLHIV with HF in SSA, similar to findings from North America (65,76). Up to one-third of African HIV-infected children have LVSD (63,64). Cardiac dysfunction in HIV-exposed infants is identifiable shortly after birth in high-income countries (77).…”
Section: Epidemiology Of Hiv-associated Hf In Lmics In the Art Eramentioning
confidence: 99%
“…Ventricular dimensions and mass are large in PLHIV with HF in SSA, similar to findings from North America (65,76). Up to one-third of African HIV-infected children have LVSD (63,64). Cardiac dysfunction in HIV-exposed infants is identifiable shortly after birth in high-income countries (77).…”
Section: Epidemiology Of Hiv-associated Hf In Lmics In the Art Eramentioning
confidence: 99%
“…Among HIV-infected children aged 18 months to 12 years with no prior cardiac problems in a tertiary teaching hospital in Nigeria, although 84% were receiving HAART, 33.7% were found to have dilated cardiomyopathy and 14.5% had pericardial effusion ≥ 5.0 mm. [4] The US National Institutes of Health (NIH) Multicenter Pediatric HIV/AIDS Cohort Study (PHACS) found that among children receiving long-term HAART, 10% had an extreme left ventricle (LV) dimension, increased aortic valve area or diameter, or a reduction of left ventricular ejection fraction (LVEF). [5] Children with HIV infection had increased carotid intima-media thickness (cIMT) compared to normal children.…”
Section: Introductionmentioning
confidence: 99%
“…The burden of cardiac dysfunction has been reportedly high among ART naïve children in Uganda and elsewhere [68]. There is paucity of data that elaborates on both conduction and functional cardiac abnormalities among ART experienced children in Uganda and other Sub Saharan African countries.…”
mentioning
confidence: 99%